ANALISA KEUANGAN DAN FAKTOR-FAKTOR YANG MEMENGARUHI PRODUKSI BAWANG MERAH DI KECAMATAN SAPE, KABUPATEN BIMA, NTB - YUSUF, M.; ASASANDI, IGN ARYAWAN (GANEC SWARA, 2024)
In 2023, Sape Regency will produce 20,081 tons of shallots, up from 19,986 tons in 2020. However, the financing of agricultural businesses is affected by a number of problems at the farmer level. The objectives of this research are as follows: (1) evaluate the financial value and income of shallot farming enterprises in Sape District, Bima Regency, NTB; (2) examine the variables influencing the production of shallot crop in Sape District, Bima Regency. Surveys were used to collect data and analyze it using descriptive analysis. According to research results, during the planting season, the cultivation of shallots in Sape Regency produces a profit of IDR 12,954,665 per cultivated land area or IDR 32,386,662 per hectare. Shallot cultivation has a B/C value of 0.13, more than 0. Therefore, it is useful to develop shallot cultivation in Sape Regency; (2) land area, seed costs, SP36 fertilizer costs, organic fertilizer costs, NPK fertilizer costs, urea fertilizer costs and ZA fertilizer costs are factors influencing shallot agricultural production in Sape District, Bima Regency. In reality, shallot production is (very) influenced by the cost of seeds and insecticides. However, shallot production is not influenced by land area, labor costs, SP36 fertilizer, organic fertilizer, NPK fertilizer, urea fertilizer, ZA fertilizer or other fertilizer costs.